The importance of the cover in The New Yorker to interpret the Covid19 crisis - Arroyo Almaraz, Isidoro; Hernández de Miguel, Paula; Liberal Ormaechea, Sheila (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
We present an empirical research work where we analyze the use of illustration in a specific medium (The New Yorker) to contrast the power of transmission of the message in a very specific context such as that of the global pandemic due to the spread of covid- 19. Methodology: A methodological triangulation has been carried out combining various techniques and tools such as documentary research, descriptive analysis, focus group and content analysis. Results: The analysis of 347 covers reveals that the element that varies from one publication to another is the illustration.